2019
DOI: 10.1002/ijc.32277
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory roles of long noncoding RNAs implicated in cancer hallmarks

Abstract: Cancer cells acquire numerous biological properties (designated “cancer hallmarks”), such as cell survival and energy metabolism, that facilitate tumor growth and metastatic dissemination during development. To date, eight hallmarks of cancer have been identified that provide a logical framework for understanding the remarkable diversity of neoplastic diseases, as proposed by Douglas Hanahan and Robert A. Weinberg. Long noncoding RNAs (lncRNAs), a category of transcripts widely demonstrated to exert significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
79
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 177 publications
(258 reference statements)
0
79
0
1
Order By: Relevance
“…Recent advances in sequencing technologies revealed that less than 2% of the human genome is encoded into proteins and approximately 90% of the human genome is transcribed actively (4). Most of the human RNA transcripts are noncoding RNAs (≥80%) (4,5),which play important functions in the different biological processes (4). Long noncoding RNAs (lncRNAs) are noncoding regulatory RNAs and have 200nt or more in length (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent advances in sequencing technologies revealed that less than 2% of the human genome is encoded into proteins and approximately 90% of the human genome is transcribed actively (4). Most of the human RNA transcripts are noncoding RNAs (≥80%) (4,5),which play important functions in the different biological processes (4). Long noncoding RNAs (lncRNAs) are noncoding regulatory RNAs and have 200nt or more in length (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the human RNA transcripts are noncoding RNAs (≥80%) (4,5),which play important functions in the different biological processes (4). Long noncoding RNAs (lncRNAs) are noncoding regulatory RNAs and have 200nt or more in length (4)(5)(6). About 4-9 % of the mammalian genome is transcribed into lncRNAs, which is higher than proteincoding mRNAs, but they have lower expression levels (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in sequencing technologies revealed that approximately 90% of the human genome is transcribed actively [5]. Most of the human RNA transcripts are non-coding RNAs (≥80%) [5,6] which perform important functions in different biological processes [5]. Long non-coding RNAs (lncRNAs) are regulatory non-coding RNAs longer than 200 nucleotides [7].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Recently, more and more studies have shown that lncRNA plays an important role in the occurrence and development of cancer due to its transcription abnormalities, epigenetic modification abnormalities or chromosomal abnormalities. 12,13 In NSCLC, it was also found that lncRNA was associated with poor tumor prognosis, and a number of lncRNAs have been found to affect the development of NSCLC as oncogenes or tumor suppressor genes. 14,15 It was reported that lncRNA THUMPD3-AS1 (THUMPD3 antisense RNA 1) was upregulated in lung cancer; however, the regulatory mechanism of THUMPD3-AS1 is not yet clear.…”
Section: Introductionmentioning
confidence: 99%